(untitled) (Research, Society and Development, 2021)
The neurosyphilis affects the Central Nervous System and can cause a number of prejudices including language, speech, orofacial and praxis. The present study aimed at describe a clinic case of a young patient with neurosyphilis and the alterations in the speech, language and neuropsychological evaluations. RSS, male, 22 years old, 11 years of education, was sent to evaluation with history of paresthesia, muscular strength loss and progressive cognitive decline. The evaluation was made through the Mini-Mental Status Examination, Montreal-Toulouse Language Assessment Battery, ASHA-FACS, Apraxia Speech Assessment Protocol and the Brief Neuropsychological Assessment Battery - NEUPSILIN. The patient presented low performance in all the evaluations. Being diagnosed with apraxia of speech, hypokinetic dysarthria and linguistic and extralinguistic disorders. It is important that for the diagnosis and adequate therapeutic planning, all the difficulties of neurological alterations are known and how much the patient is affected by these symptoms.